Endoscopy Instruments Their Role in Delivering Optimal Patient Care - Shrubb, Jane (Operating Room Nurses Association of Canada Journal, 1994)
It is imperative to have available proper, functioning, sterile instruments for surgical procedures to decrease the opportunity for intra and post operative patient complications: Maintain patient safety, Decrease time patient is under anaesthesia, and Achieve a zero infection rate.